Profil Kemampuan Literasi Matematis Siswa pada Materi Program Linear Ditinjau dari Gaya Berpikir Gregorc - Utami, Lintang Fitra; Hardianti, Desrina; Rahayu, Chika; Asyhara, Suryatul Aini (Program Studi Pendidikan Matematika FIP UNHASY, 2026)
This study aims to describe mathematical literacy abilities as viewed through Gregorc’s thinking styles, which are classified into four types: concrete sequential (CS), abstract sequential (AS), concrete random (CR), and abstract random (AR). This study is a qualitative descriptive study. Subjects were selected using purposive sampling from a population of 23 11th-grade MIPA students. The sample consisted of two students representing each thinking style category. Data collection techniques included a mathematical literacy test and the Gregorc thinking style questionnaire. The results of this study indicate that CS and AA students generally able to construct models, apply them, and interpret results, but they still lack precision. AS students tend to be less systematic and less accurate in their problem-solving, while CR students still struggle to understand information and determine solutions. Overall, differences in thinking styles influence students’ precision, thoroughness, and accuracy in solving mathematical problems.